Aplikasi Sistem Informasi Keuangan di SMAN 1 Pare - Tommy Mandala Suherman; Adi Wibowo; Silvia Rostianingsih (Jurnal Infra, 2017)
Currently, SMAN 1 Pare report information using Microsoft Excel. This causes makes user difficult to create a final report, where all the list of activities will be sorted by category. This application is made to facilitate the admin in making financial informations where the application will automatically create reports based on categories without being separated again by the user.This application is created using the programming language HTML, PHP and MySQL database. Display this app using SBAdmin with Bootstrap. This app has features, proposal, budget plan, purchases, in and out of warehouse, student payroll and payroll.From the test results, applications that have been made to process financial transaction data into various kinds of reports required by schools automatically. The app can also display data to all users as per their access rights.